A stylometric reading of William Wordsworth and W. B. Yeats’s poetry: Ambivalent cravings in romantic and modernist consciousness - Kusi, David Toh (Research Journal in Advanced Humanities, 2022)
What is peculiar about William Wordsworth and William Butler Yeats is that they represent two variants of the same type of consciousness. Their awareness of the world is linked to aesthetic appreciations. This paper explores this aesthetics with emphasis on the poets’ believe that art, specifically poetry, is an instrument of vision through which nature and humanity, can be appreciated and made perfect. While it is observed that very little has been written comparing Wordsworth and Yeats, this comparative critical assessment juxtaposes these self-seeking poets focusing on their ambivalent romantic yearnings. Stylometric methods with Voyant tools and “R-Stylo” are applied for quantitative and qualitative analyses of the poets’ ambivalent cravings. The question that runs through the paper is how both poets, in the context of periodization do, transcend their eras to establish visionary dimensions of the romantic quest. The results found in the analysis of both poets’s sublime consciousness display to a certain extent the representation of the artists’ contrasting moods. Such moods, however, reveal them as literary connoisseurs who transcended the boundaries of periodization and concentrated on cultural, historical, ideological and philosophical realities as means to rescue mankind from prolong affliction and psychical strain.